Methodological Approaches to the Prevention Of Schoolgirls' Deviant Behavior - Ivanna Parfanovych (Vasyl Stefanyk Precarpathian National University, 2017)
The methodological approaches to the system of girls' deviant behavior prevention thatact on different levels on prevention are identified: gender, personality oriented, systematic,synergetic, security and safety, interdisciplinary, institutional, which are provided at differentlevels of prevention. Methodological approaches were applied while developing the design,implementing and analyzing of schoolgirls deviant behavior prevention. Such approaches canbe implemented in practice, if the realities of girls' socialization in various areas and theproblem are treated from the socio-pedagogical point of view. Key words: schoolgirls, deviant behavior, prevention, methodological approaches.